2008
DOI: 10.1002/jcp.21510
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and degradation of heparin is not required for stimulus of heparan sulfate proteoglycan synthesis

Abstract: In vitro, heparin and antithrombotic drugs specifically stimulate the synthesis of an antithrombotic heparan sulfate proteoglycan (HSPG) produced by endothelial cells. The putative heparin binding site(s) that may be related to this phenomenon were investigated. In the preceding article, using various heparin probes, it was shown that the heparin does not bind to the endothelial cell surface, but only to the extracellular matrix. The present study demonstrated that, when the cells were exposed to heparin at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…To enable heparin-free cell culture, fibrinogen was depleted mechanically from pHPL-based medium as described 33 and stromal cells were cultured in the presence and absence of heparin. By flow cytometry and immunocytochemistry a distinct cellular internalization of fluoresceinamine-labeled heparin mainly in the lysosomal compartment could be detected as described previously for other cell types 3438 . Comparing gene and protein expression profiles of stromal cells from BM, UC and WAT in the presence and absence of heparin we observed distinct significantly influenced sets of genes, signaling cascades and proteins as well as posttranslational phosphorylation of proteins associated with WNT, PDGF, NOTCH and TGFbeta signaling pathways.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…To enable heparin-free cell culture, fibrinogen was depleted mechanically from pHPL-based medium as described 33 and stromal cells were cultured in the presence and absence of heparin. By flow cytometry and immunocytochemistry a distinct cellular internalization of fluoresceinamine-labeled heparin mainly in the lysosomal compartment could be detected as described previously for other cell types 3438 . Comparing gene and protein expression profiles of stromal cells from BM, UC and WAT in the presence and absence of heparin we observed distinct significantly influenced sets of genes, signaling cascades and proteins as well as posttranslational phosphorylation of proteins associated with WNT, PDGF, NOTCH and TGFbeta signaling pathways.…”
Section: Introductionsupporting
confidence: 58%
“…1C). Since data exist indicating that heparin is internalized by lysosomes 38,40 , we next incubated UC-derived stromal cells simultaneously with F-heparin and LysoTracker. Z-stack images obtained by confocal laser microscopy indicated that heparin’s intracellular distribution was associated with lysosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All assays performed corroborate with cytotoxicity assays, in which a higher uptake cellular was observed when the lauryl gallate loaded in superparamagnetic PMMA nanoparticles surface modified with FA was incubated at 37 °C. When the nanoparticles were incubated at 4 °C, assuming that the energy-dependent pathways are inhibited, the nanoparticles were not able to diffuse at 4 °C, suggesting that the nanoparticles were uptake by some energy-dependent pathways [62][63][64]. Lastly, our results suggest that the higher cellular uptake observed by confocal microscopy and flow cytometry of lauryl gallate loaded in superparamagnetic PMMA nanoparticles surface modified with FA were delivered into HeLa cells via folate receptor-mediated endocytosis.…”
Section: In Vitro Cytotoxicity and Cellular Uptakementioning
confidence: 93%
“…The synthesis of sulfated glycosaminoglycans was assessed as described previously (Trindade et al, 2008a), in the presence or absence of cell signaling pathway inhibitors: 10 µM PD98059 (Calbiochem, USA); 25 µM FPT II (Calbiochem/Merk, Darmstadt, Germany); 10 µM KN‐62 (Sigma‐Aldrich, St Louis, MO); 10 µM 2‐APB (Calbiochem); 5 µM U73122 (Tocris, Bristol, UK); 10 µM BAPTA/AM (Invitrogen, Carlsbad, CA); 10 µM LNNA (Tocris, Bristol, UK) (Gazit et al, 1989; Grote et al, 2007; Paredes‐Gamero et al, 2010). The concentration of 100 µg/ml was used since it induces the maximal up‐regulation in the expression of HSPG (Nader et al, 1989, 1991).…”
Section: Methodsmentioning
confidence: 99%